Pelatihan Penulisan Karya Ilmiah Pada Guru Di SMK Sumatera Selatan - Kanada, Rabial; Zulkipli, Zulkipli (Universitas Muhammadiyah Sidenreng Rappang, 2024)
Writing scientific papers is an obligation and a necessity for teachers. The work of science is a requirement for promotion to the rank of teacher. More than that, scientific work is a place for teachers to express thoughts related to the knowledge they are involved in. Writing scientific papers is also a forum for promoting schools where teachers work. But in fact there are still many teachers who are not familiar with scientific work. The holding of community service activities is expected to be able to improve teachers' abilities in writing scientific papers. The PkM activity method is in the form of technical guidance with partners from the Faculty of Tarbiyah and Teacher Training UIN Raden Fatah, with 1 resource person. The results obtained are an increase in the ability to write scientific papers, especially scientific papers in scientific journals. Judging from the teacher's understanding of the scientific work of scientific journals, the characteristics of scientific journal works and understand the process of submitting and publishing. With an average pre-test score of 55 to an average post-test score of 84. The activity participants participated 100% actively and gave positive responses during the technical guidance. Thus this community service activity is useful for increasing the ability of teachers regarding writing scientific papers.